2017
DOI: 10.1097/ccm.0000000000002451
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound as a Screening Tool for Central Venous Catheter Positioning and Exclusion of Pneumothorax*

Abstract: Transthoracic echocardiography and lung ultrasound are noninferior to chest x-ray for screening of pneumothorax and accurate central venous catheter positioning. Thus, the point of care use of ultrasound can reduce central venous catheter insertion to use time, exposure to radiation, and improve patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 19 publications
0
44
0
1
Order By: Relevance
“…214,215 Observational studies also demonstrate that transthoracic ultrasound can confirm residence of the guidewire in the venous system (Category B3-B evidence). [216][217][218][219] One observational study indicates that transesophageal echocardiography can be used to identify guidewire position (Category B3-B evidence), 220 and case reports document similar findings (Category B4-B evidence). 221,222 Observational studies indicate that transthoracic ultrasound can confirm correct catheter tip position (Category B2-B evidence).…”
Section: Catheter Maintenancementioning
confidence: 97%
“…214,215 Observational studies also demonstrate that transthoracic ultrasound can confirm residence of the guidewire in the venous system (Category B3-B evidence). [216][217][218][219] One observational study indicates that transesophageal echocardiography can be used to identify guidewire position (Category B3-B evidence), 220 and case reports document similar findings (Category B4-B evidence). 221,222 Observational studies indicate that transthoracic ultrasound can confirm correct catheter tip position (Category B2-B evidence).…”
Section: Catheter Maintenancementioning
confidence: 97%
“…Furthermore, chest US is very useful to rule out PTX after an interventional procedure (ie, transbronchial lung biopsy, central venous catheter insertion and medical thoracoscopy) …”
Section: Chest Ultrasound Findingsmentioning
confidence: 99%
“…Ultrasound identified important lung pathology that was missed by conventional assessment in 20% of patients, with the largest difference being in the detection of interstitial alveolar syndrome and the smallest difference being in detection of pleural effusion. Amir et al . also demonstrated that during central venous catheter insertion, TTE and lung ultrasound could substitute chest radiography for identifying the central venous catheter tip and excluding pneumothorax.…”
Section: The Breadth Of Perioperative Ultrasoundmentioning
confidence: 99%